Designing Environmentally Friendly Drainager Systems In Flood-Potential Urban Areas - Mohamad Djaelani (Universitas Muhammadiyah Palu, 2024)
Rapidly growing urban areas often face flooding issues caused by inadequate drainage management. This article discusses the design of an environmentally friendly drainage system as a solution to address flooding problems in urban areas. The environmentally sustainable drainage system focuses on the principles of sustainability and utilizes natural elements to reduce the negative impacts of flooding. This study explores various approaches that can be applied in designing drainage systems in flood-prone urban areas. The expected outcome is an efficient, environmentally friendly, and sustainable drainage system.